Analysis of Factors that Influence Generation Z Job Selection Considerations in Madiun City - Mila Eviana; Karuniawati Hasanah (JMM17 : Jurnal Ilmu ekonomi dan manajemen, 2023)
This research aims to analyze factors that influence job selection considerations including salary offer, career level, interests, working hours, location, relevant education undertaken, work environment, parental influence, job prospects, professional training, social values , personality, job market considerations, and motivation. The data source in this research was obtained by conducting research on Generation Z respondents in Madiun City by distributing questionnaires via Google Form. This type of research is descriptive research with a quantitative approach. Sampling was carried out using the Slovin formula with a sample of 375 respondents. The data analysis technique uses test equipment in the form of IMB SPSS 16 software. The results of this research show that the salary offer, career level, interests, working hours, location, relevant education undertaken, work environment, parental influence, job prospects, professional training, Social values, personality, job market considerations, motivation influence Generation Z in selecting jobs in the city of Madiun, but there is 1 factor, namely salary offer, which is the dominant factor which has the greatest influence compared to other factors.